Additional Food Supplementation Of High Animal Protein Food, Calcium, And Zinc In Children Aged 6-24 Months As An Effort To Increase Children's Body Length - Wiyono, Sugeng; Muntikah, Muntikah; Meilinasari, Meilinasari (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
The 2021 Basic Health Research (Riskesdas) results of the Ministry of Health of the Republic of Indonesia show that stunting prevalence in five-year-old children is 24.4%. Children who are stunted until the age of 5 years will find it challenging to overcome, so it will continue into adulthood and can increase the risk of offspring with low birth weight. Stunting will cause long-term impacts, namely impaired physical, mental, intellectual, and cognitive development. This research method used true experimental design by providing 50,0 g of nuggets daily for six weeks as high supplements in animal protein, calcium, and zinc. The subjects of this research were children aged 6-24 months, the subjects were randomly assigned. The number of samples based on the sample size calculation was 30 children. Bodyweight was measured using a digital scale, and body length/height was measured using a stadiometer and microtoice. Data was processed and analyzed using computerized statistical software. The results showed that before the intervention was given to the treatment subjects, the average height was 79,6 ± 4,8 cm; after the treatment, the average height was 80,01±4,9 cm. Based on the paired t-test results, there was a significant difference in height of 0,41 ± 0,26 cm (p = 0,000). For initial body weight or before being given treatment to the treatment subjects, there was an average body weight of 10,1 ± 1,5 kg, and after being given treatment, the average body weight was 10,3±1,5 kg, there was no difference (p = 0,082) of body weight after being given supplementation. As a suggestion, it is necessary to develop a more varied form of food so that infants and children of all ages can consume high amounts of supplements in animal protein, calcium, and zinc.